Evaluation of an igm enzyme-linked immunosorbent assay ( ELISA) ) test for the rapid dignosis of dengue virus infection among febrile children in Sri Lanka - Sivananthan, K (My University, 1998)
This study was conducted to evaluate the dengue specific igm elisa antibody test,which is sample and easy to perform.A total number of 86 children below 12 years of age who attended the out patient department(OPD) of the lady ridgway hospital with a histroy of one -four days fever without any respiratory signs were enrolled in this study.Acute boold samples collected from all 86 patients were tested by virus isolation and igm elisa:22 (25.6 per cent) were positive by isolation and 6 (7 per cent) by igm elisa.Of these 6,3 cases were diagnosed as past infection,when the convalescent bloods were tested.Multiple dengue serotypes (D1,D2,D3) were isolated with D2 preominating.Both sexes were equally affected with more cases being detected in the 5-9 year age group.Igm elisa was found to be the most sensitive test but had a low positivity rate (7 per cent) in the acute samples and also had 2.7 per cent false positives.Ideally this test should be carried out on samples collected after the 5 th day of onset of illness,preferably after the first week.If these samples are negative,dengue virus infection can be excluded.